Modeling suitable habitats of stingless bee klanceng (Tetragonula laeviceps) in Merbabu Mountain areas related to elevation, temperature, and humidity variables - Atmaja, Cornelius Devito; Sukirno, Sukirno; Purwanto, Hari; Andriwibowo, Andriwibowo; Prabowo, Hanindyo Adi (Foresty Faculty of Hasanuddin University, 2024)
Klanceng is one of the stingless bee species in Indonesia with the scientific name Tetragonula laeviceps. This bee species has sustainable economic values since it has a role as a pollinator. This species is also common in mountainous areas, including Merbabu Mountain, Central Java. Despite this bee being very common, information about potential distributions of this bee is very limited, and this information is needed for its management. This study aimed to model the potential habitat for T. laeviceps using species distribution modeling (SDM) with elevation, temperature, and humidity as predictors. The model was built based on the T. laeviceps occurrence points gained through field surveys, with a total of 23 sampling points. According to the model, most of the west parts of Merbabu Mountain were considered not suitable for T. laeviceps. This suitability is also similar to the north and south parts. This condition is in contrast to the areas that bordered with the Merbabu Mountain directly. Most areas adjacent to the Merbabu Mountain were having high and very high suitability for T. laeviceps. Regarding altitudinal distribution, T. laeviceps was limited at elevations of 1000 m.